Binarna i ternarna relacja uczestników procesu diagnostyczno-terapeutycznego w logopedii - Kaźmierczak, Monika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The article points out that the problem of the main binary relation in speech-language therapist (therapist-patient) and the interrelated relationship (speech-language therapist-patient-family/carer) should be addressed with respect to dialogue personalization, respecting the autonomy of each participant in speech-language therapy as well as the specificity of the primary group (family) and secondary (organizational, contractual). The sequence of appropriate interactions, that is, the interactions of the main actors of the diagnostic and therapeutic process, can transform into a lasting relationship and thereby influence the progress in speech-language therapy and the quality of the patient's life, if personal contacts and language announcements are reciprocated with kindness, respect and willingness partner collaboration.